1999
DOI: 10.1034/j.1399-3003.1999.14c29.x
|View full text |Cite
|
Sign up to set email alerts
|

Inner city air pollution and respiratory health and atopy in children

Abstract: The impact of inner city air pollution on the development of respiratory and atopic diseases in childhood is still unclear.In a cross sectional study in Dresden, Germany, 5,421 children in two age groups (5±7 yrs and 9±11 yrs) were studied according to the International Study of Asthma and Allergies in Childhood (ISAAC) phase II protocol. The prevalences of wheezing and cough as well as doctor diagnosed asthma and bronchitis were assessed by parental questionnaires. Children also underwent skin-prick testing, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
139
5
6

Year Published

2002
2002
2013
2013

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(167 citation statements)
references
References 24 publications
(51 reference statements)
17
139
5
6
Order By: Relevance
“…Ozone may cause a small increase in reported respiratory symptoms of cough and bronchitis at peak levels greater than 160 μg/m 3 (Braun-Fahrlander et al, 1997). Diesel exhaust emissions have been associated with increased reporting of cough and nonspecific respiratory symptoms in children (Nakatsuka et al, 1991;Nitta et al, 1993;Wjst et al, 1993;Oosterlee et al, 1996;Hirsch et al, 1999). Children living in close proximity to major freeways with high truck density experience increased cough, wheeze, and rhinitis , and children less than two years of age may be the most vulnerable (Gehring et al, 2002).…”
Section: ) Ambient Airmentioning
confidence: 99%
“…Ozone may cause a small increase in reported respiratory symptoms of cough and bronchitis at peak levels greater than 160 μg/m 3 (Braun-Fahrlander et al, 1997). Diesel exhaust emissions have been associated with increased reporting of cough and nonspecific respiratory symptoms in children (Nakatsuka et al, 1991;Nitta et al, 1993;Wjst et al, 1993;Oosterlee et al, 1996;Hirsch et al, 1999). Children living in close proximity to major freeways with high truck density experience increased cough, wheeze, and rhinitis , and children less than two years of age may be the most vulnerable (Gehring et al, 2002).…”
Section: ) Ambient Airmentioning
confidence: 99%
“…Air pollution is convincingly associated with many signs of asthma aggravation, including pulmonary function decrements, increased AHR, visits to emergency departments, hospital admissions, increased medication use, and reported symptoms; it is also associated with inflammatory changes, interactions between air pollution and allergen challenges, and immune symptom changes. 33 A significant association between trafficrelated air pollution and wheeze has also been reported in children, 34,35 and exposure to diesel exhaust particles may reduce lung function in children living near motorways. Long-term exposure to ambient ozone has been associated with the development of asthma in adult males.…”
Section: Epidemiologic Studiesmentioning
confidence: 99%
“…Hirsch et al (65) recently found an association between CO and other pollutants and respiratory symptoms in children. Ritz and Yu (70) found an association between 3-month average maternal exposures to CO and low birth weight.…”
Section: Carbon Monoxidementioning
confidence: 99%
“…Researchers have found increased morbidity to be associated with long-term exposure to NO 2 , for decreased lung function (38,58,65,66), increased respiratory symptoms or illness (41,46,65,(67)(68)(69), and increased symptoms in children with asthma (47).…”
Section: Nitrogen Dioxidementioning
confidence: 99%
See 1 more Smart Citation